Perception of the Łódź Industrial Architecture Route by its inhabitants: An example of social participation in tourism research - Jaśkiewicz, Anna (Turyzm/Tourism, 2017)
Łódź as a post-industrial city has great potential for post-industrial tourism. An attempt to utilise this has been the creation of the Łódź Industrial Architecture Trail, bringing together buildings related to its industrial past. According to the author, to make the trail a tourist attraction, the first people who should be aware of its value are the city’s inhabitants. The survey confirmed the very important role of social participation in creating the image of a city, and providing the basis for further work on its improvement and promotion. The article does not cover social participation as part of the process of development, but can serve as a contribution to a discussion of the role of a city’s inhabitants in shaping its tourism attractions. At the same time, the article confirms that social participation is an extremely important element of tourism research and forms an introduction to its effective use in practice.